CD326 (EpCAM) testing by flow cytometric BerEP4 antibody is a useful and rapid adjunct to histopathology. Issue 3 (28th July 2017) - Dorwal, Pranav; Moore, Helen; Stewart, Pam; Harrison, Barbara; Monaghan, Julie
Abstract : Flow cytometry has been traditionally used to diagnose leukaemia and lymphoma in peripheral blood, bone marrow, body fluids, and tissue samples. The diagnosis of a malignant epithelial tumour is usually made by correlation between histopathologic appearance and the use of immunohistochemical staining. A CE approved BerEP4 antibody (anti‐EpCAM, CD326) is available for flow cytometric testing, but has been evaluated predominantly in body fluids in the current literature. In this study, we have evaluated the performance of this antibody in detecting the presence of epithelial cells in tissue samples which have traditionally been reported as CD45 negative cells by flow cytometry. Among the 42 cases studied, 21 (50%) were found to be positive for CD326, thereby suggesting epithelial differentiation. The results had good concordance rates (97.6%) with final histopathological diagnosis. The results clearly show that flow cytometric testing for BerEP4 (CD326) can be a useful method for diagnosing nonhaematological malignancies that are poorly differentiated. As this is a rapid method for identifying epithelial differentiation, it can help the histopathologists tailor and rationalise the immunohistochemical panel, with the potential benefits of improving reporting times and work‐flow in the laboratory. © 2017 International Clinical Cytometry Society